Evaluation of mutagenicity and metabolism-mediated cytotoxicity of the naphthoquinone 5-methoxy-3,4-dehydroxanthomegnin from Paepalanthus latipes - Kitagawa, Rodrigo R.; Vilegas, Wagner [UNESP]; Varanda, Eliana A. [UNESP]; Raddi, Maria S. G. [UNESP] (Soc Brasileira Farmacognosia, 2015)
A large number of quinones have been associated with antitumor, antibacterial, antimalarial, and antifungal activities. Results of previous studies of 5-methoxy-3,4-dehydroxanthomegnin, a naphthoquinone isolated from Paepalanthus latipes Silveira, Eriocaulaceae, revealed antitumor, antibacterial, immunomodulatory, and antioxidant activities. In this study, we assessed the mutagenicity and metabolism-mediated cytotoxicity of 5-methoxy-3,4-dehydroxanthomegnin by using the Ames test and a microculture neutral red assay incorporating an S9 fraction (hepatic microsomal fraction and cofactors), respectively. We also evaluated the mutagenic activity in Salmonella typhimurium strains TA100, TA98, TA102, and TA97a, as well as the cytotoxic effect on McCoy cells with and without metabolic activation in both tests. Results indicated that naphthoquinone does not cause mutations by substitution or by addition and deletion of bases in the deoxyribonucleic acid sequence with and without metabolic activation. As previously demonstrated, the in vitro cytotoxicity of 5-methoxy-3,4-dehydroxanthomegnin to McCoy cells showed a significant cytotoxic index (CI50) of 11.9 mu g/ml. This index was not altered by addition of the S9 fraction, indicating that the S9 mixture failed to metabolically modify the compound. Our results, allied with more specific biological assays in the future, would contribute to the safe use of 5-methoxy-3,4-dehydroxanthomegnin, compound that has showed in previous studies beneficial properties as a potential anticancer drug. (C) 2014 Sociedade Brasileira de Farmacognosia. Published by Elsevier Editora Ltda. All rights reserved.
Keywords: Cytotoxicity; 5-Methoxy-3,4-dehydroxanthomegnin; Mutagenicity